Tolstoy, Universalism and the World Religions. Issue 3 (9th January 2017) - MOULIN, DANIEL
Abstract : Leo Tolstoy was one of the most prolific religious figures of his time. Yet his religious thought and its influence have seldom been explored by church historians. Drawing upon themes within his literature, non-fiction and previously unconsidered primary sources, this paper considers Tolstoy's religious position in relation to other similar nineteenth-century religious movements. It exposes Tolstoy's links with British Unitarians and also considers Tolstoy's influence upon the founder of Britain's first interfaith organisation, the World Congress of Faiths. It is argued that Tolstoy provides a paradigmatic example by which to examine the relationship between the legacy of the Enlightenment and changing attitudes towards non-Christian religions.